2009
DOI: 10.1037/a0014273
|View full text |Cite
|
Sign up to set email alerts
|

Therapist-aided exposure for women with lifelong vaginismus: A replicated single-case design.

Abstract: Vaginismus is commonly described as a persistent difficulty in allowing vaginal entry of a penis or other object. Lifelong vaginismus occurs when a woman has never been able to have intercourse. A replicated single-case A-B-phase design was used to investigate the effectiveness of therapist-aided exposure for lifelong vaginismus. A baseline period (Phase A) was contrasted with exposure + follow-up (Phase B), using random switching between phases. The main outcome measure (intercourse ability) was assessed dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 23 publications
6
85
0
1
Order By: Relevance
“…What follows will illustrate the functionality of the package with an example from ter Kuile et al (2009). A more detailed manual can be found in the Appendix.…”
Section: • Combine P-valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…What follows will illustrate the functionality of the package with an example from ter Kuile et al (2009). A more detailed manual can be found in the Appendix.…”
Section: • Combine P-valuesmentioning
confidence: 99%
“…Ter Kuile et al (2009) investigated the effectiveness of therapist-aided exposure for lifelong vaginismus. Lifelong (or primary) vaginismus occurs when a woman has never been able to have sexual penetrative intercourse during her whole life.…”
Section: • Combine P-valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine out of ten participants reported having had penilevaginal intercourse after treatment and in five out of nine responders, intercourse was accomplished within the first week of treatment. These results remained at a 1 year follow-up (ter Kuile et al, 2009). A subsequent randomized, waiting-list controlled study (N = 50) of women with lifelong vaginismus demonstrated that, after the exposure week, 80% of the treated women were able to have intercourse, again compared with none in the waiting-list condition.…”
mentioning
confidence: 96%